Automatic exchange of financial information from the perspective of tax fairness and transparency - Isnaini Isnaini; Joni Emirzon; Ridwan Ridwan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Tax fairness and transparency concepts have gained increasing prominence in the global tax and financial regulatory landscape in recent years. Automatic Exchange of Financial Information (AEOI) has proven to be an effective tool for implementing these principles. The aim of this study is to contribute to the ongoing international tax discussion and facilitate further research on the multiple dimensions of tax fairness and transparency in the global financial ecosystem. The type of research used is normative legal research. The results show that AEOI can help prevent tax evasion, ensure taxpayer compliance, and strengthen international cooperation in the fight against tax evasion and fraud. Challenges such as data security and compliance costs can be addressed with the development of better technology and regulatory frameworks. AEOI reflects countries' vision for tax fairness and transparency that supports social welfare and economic stability.